Intravascular imaging and computer assisted stenting, and large-scale annotation of biomedical data and expert label synthesis : 6th Joint International Workshops, CVII-STENT 2017 and second International Workshop, LABELS 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 10-14, 2017, Proceedings /: 6th Joint International Workshops, CVII-STENT 2017 and second International Workshop, LABELS 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 10-14, 2017, Proceedings. (2017) - Unknown
No abstract available